2020
DOI: 10.3389/fimmu.2020.01273
|View full text |Cite
|
Sign up to set email alerts
|

Role of MIF Cytokine/CD74 Receptor Pathway in Protecting Against Injury and Promoting Repair

Abstract: Wound healing after an injury is essential for life. An in-depth understanding of the healing process is necessary to ultimately improve the currently limited treatment options for patients suffering as a result of damage to various organs and tissues. Injuries, even the most minor, trigger an inflammatory response that protects the host and activates repair pathways. In recent years, substantial progress has been made in delineating the mechanisms by which inflammatory cytokines and their receptors facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(118 citation statements)
references
References 108 publications
4
101
0
Order By: Relevance
“…It is highly involved in the antigen presentation and the activation of CD4 + T cells ( Cresswell, 1994 ). CD74 is the cell surface membrane receptor for the cytokine macrophage migration inhibitory factor (MIF) ( Farr et al, 2020 ). The role of the interaction between CD74 and MIF has been revealed in different types of cancers ( Binsky et al, 2007 ; Nagata et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is highly involved in the antigen presentation and the activation of CD4 + T cells ( Cresswell, 1994 ). CD74 is the cell surface membrane receptor for the cytokine macrophage migration inhibitory factor (MIF) ( Farr et al, 2020 ). The role of the interaction between CD74 and MIF has been revealed in different types of cancers ( Binsky et al, 2007 ; Nagata et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a pleiotropic inflammatory cytokine produced by immune cells and non-immune cells ( Bilsborrow et al, 2019 ), play an important role in the inflammatory response and immune regulation ( Calandra and Bucala, 1997 ; Burger et al, 2002 ). Ample evidence shows that MIF is involved in the regulation of heart function under pathological conditions, including burns, diabetes and I/RI ( Pohl et al, 2016 ; Yu et al, 2019 ; Farr et al, 2020 ). Studies have also confirmed that MIF plays a crucial role in myocardial protection by ischemic preconditioning ( Ruze et al, 2019 ), Ischemic preconditioning activates RISK and AMPK signal pathways through MIF, reduced myocardial infarction area and cardiomyocyte apoptosis ( Dow et al, 2012 ; Emontzpohl et al, 2019 ), inhibition of ROS production ( Yang et al, 2010 ) and inflammatory infiltration of cells, maintained endothelial cell function ( Argaud et al, 2005 ), thereby improving cardiac dysfunction caused by myocardial I/RI ( Vinten-Johansen et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…We are not currently able to determine whether the inverse correlation of MIF and inflammation represents an epiphenomenon, associated to the wound healing processes that follow the acute inflammatory phases, or whether MIF actually takes place in regulating inflammation in the skin. It is of interest in this setting that recent evidences indicate a key role of the MIF/CD74 cell signaling pathway in regulating wound healing after injury [ 37 ]. However, it should also be noticed that MIF is mainly produced byTh2 cells, rather that Th1 cells [ 38 ], hence, it may take a role in the resolution phase of the disease.…”
Section: Discussionmentioning
confidence: 99%